MANAJEMEN KEPALA MADRASAH DALAM PENGEMBANGAN PROFESIONALISME GURU PENDIDIKAN AGAMA ISLAM (PAI) - Zainuddin, Mohammad Riza (EDUKASI: Jurnal Pendidikan Islam, 2014)
Various measures should be considered and implemented in order to improve the quality of education . Improving the quality of education is the improvement of teaching and learning process that is dependent upon the professionalism of teachers as human resources. Speaking of professional teachers, there are still many good people among experts discussed their own education or outside education experts . Even many who tend to abuse the position of teacher , whether relating to the public interest until the very personal nature . While from the teachers themselves barely able to defend themselves . Community or parents were sometimes accused of teachers lacking professional, quality and so on , when her son was not able to resolve the problem she faced alone or have the ability that does not comply with her wishes.